Estimation des parametre d’une distribution a l’aide de methodes d’optimisation - Naima Douaissia (My University, 2026)
In order to study the estimation of the parameters of a distribution using optimization methods, and to solve likelihood functions that do not have an explicit analytical solution—in other words, that are complex—this represents a powerful approach, especially when analytical estimation (such as the method of moments or the classical maximum likelihood method) is difficult or impossible to carry out explicitly. Parameter estimation of a distribution involves identifying the values that make a statistical model most consistent with the observed data. When explicit formulas for estimators are complex or non-existent, numerical optimization methods are used to maximize the likelihood function (or its logarithmic form). This approach is particularly useful for complex distributions (e.g., beta-Pareto) or when constraints are imposed on the parameters. However, it requires good initialization, convergence analysis, and sometimes regularization techniques. --------------------------------------------------في سبيل دراسة تقدير معلمات توزيع إحصائي باستخدام طرق التحسين العددي، ومن أجل حل دوال الاحتمالية) التي لا تمتلك حلاً تحليلياً صريحاً ـ أي أنها معقدة ـ تُعد هذه المقاربة أداة قوية، لا سيما عندما يكون ) التقدير التحليلي (مثل طريقة العزوم أو طريقة الاحتمالية القصوى الكلاسيكية) صعباً أو مستحيلاً تنفيذه بشكل صريح. يتمثل تقدير معلمات التوزيع في تحديد القيم التي تجعل النموذج الإحصائي أكثر توافقاً مع البيانات المرصودة. وعندما تكون الصيغ الصريحة للمقدرات معقدة أو غير موجودة، نلجأ إلى طرق التحسين العددي من أجل تعظيم دالة الاحتمالية (أو الشكل اللوغاريتمي لها). تعد هذه المقاربة مفيدة بشكل خاص للتوزيعات المعقدة (مثل توزيع بيتا-باريتو )، أو عند فرض قيود على المعلمات. ومع ذلك، فهي تتطلب تهيئة أولية جيدة، وتحليلاً دقيقاً لتقارب الحل، وأحياناً تقنيات للتنظيم (regularization). ------------------------------------------------- Dans le but d’étudier l’estimation des paramètres d’une distribution à l’aide de méthodes d’optimisation et afin de résoudre des fonctions de vraisemblance qui ne possèdent pas de solution analytique explicite autrement dit complexe, qui est une approche puissante, surtout lorsque l’estimation analytique (comme les estimateurs des moments ou la méthode du maximum de vraisemblance classique) est difficile ou impossible à effectuer de manière explicite.
Keywords: parametric estimation; Maximum Likelihood estimation(MLE); numerical optimization; conjurate gradient; convergence Monte Carlo simulations.; ق ، التحسين العددي ، EMV التقدير بأقصى احتمال ، التقدير البراميتري المعلم ي . لتقارب مح; Estimation paramétrique; EMV; optimisation numérique; gradient conjugué; convergence; simulations Monte Carlo.